Why Was There Even a Reformation in Lindau? The Myth and Mystery of Lindau’s Conflict-Free Reformation - Wolfart, Johannes (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
Histories of Lindau emphasize a remarkably conflict-free course of early reform in that particular locale. This view is established and maintained by multiple means, including hyper-credulity towards the peacefulness asserted by local authorities, anachronistic projections of the confessional “compromise” that was the Tetrapolitana back into the 1520s, and a deliberately narrow definition of key subjects, to exclude obvious contrary evidence. While Bernd Moeller has recently remarked that Lindau society was so harmonious that it is surprising there was any Reformation at all, archival sources actually indicate conflict in several areas pertaining to the early Reformation in Lindau, including interpersonal violence over key theological issues, the social conflict of the Peasant’s War, and stark communal divisions over iconoclasm, resulting in the ritual conflict of a feud. This article is both a particular historical corrective and a general historiographical illustration of how mythographic and historiographic modes may be entangled in early Reformation studies.